Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

First Report on the Asexual Morphology of Nigrograna jinghongensis (Nigrogranaceae, Pleosporales) with a New Host Record from China - Li‐Xue Mi; Hai‐Yan Song; Kevin D. Hyde; Prapassorn D. Eungwanichayapant; Ausana Mapook; Mu‐Sen Chen; Dian‐Ming Hu (New Zealand Journal of Botany, 2026)
Nigrograna jinghongensis was originally described based on sexual morphology from decaying woody litter in Yunnan Province, China. In this study, we report its asexual morph, isolated as endophytes from Tetradium ruticarpum in Anhui Province. The asexual morph of N. jinghongensis features coelomycetous pycnidia that are dark brown and globose to pyriform, bearing filiform, septate conidiophores with phialidic, hyaline conidiogenous cells, and ellipsoidal to subcylindrical, aseptate, guttulate conidia. Species identification was confirmed by multigene phylogenetic analysis using ITS, LSU, SSU, tef1‐α , and rpb2 sequences. This is the first report of the asexual morph of N. jinghongensis , expanding knowledge of its life cycle, ecological adaptability, and host association.

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Transverse and longitudinal seismic responses of a subsea shield tunnel under obliquely incident seismic waves considering structure-water-poroelastic sediment-rock dynamic interactions - Weihua Li; Yexin Wan; Hang Mu; Sen Zheng (Ocean Engineering, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

The regulation effect of urban green space on air particulate matter concentration under different matrices in Xi'an city - Bo Jiang; Shiyu Fan; Chang Sun; Sen Mu; Tian Gao; Ling Qiu (Air Quality, Atmosphere & Health, 2024)

Exploring lipid digestion discrepancies between preterm formula and human milk: Insights from in vitro gastrointestinal digestion and the impact of added milk fat - Ning Wang; Sen Yang; Guang-Qing Mu; Fang Qian; Xue-Mei Zhu (Food Research International, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Research on the Drift Prediction of Marine Floating Debris: A Case Study of the South China Sea Maritime Drift Experiment - Lin Mu; Haiwen Tu; Xiongfei Geng; Fangli Qiao; Zhihui Chen; Sen Jia; Ruifei Zhu; Tianyu Zhang; Zhi Chen (Journal of Marine Science and Engineering, 2024)
Annually, hundreds of individuals tragically lose their lives at sea due to shipwrecks or aircraft accidents. For search and rescue personnel, the task of locating the debris of a downed aircraft in the vastness of the ocean presents a formidable challenge. A primary task these teams face is determining the search area, which is a critical step in the rescue operation. The movement of aircraft wreckage on the ocean surface is extremely complex, influenced by the combined effects of surface winds, waves, and currents. Establishing an appropriate drift motion prediction model is instrumental in accurately determining the search area for the wreckage. This article initially conducts maritime drift observation experiments on wreckage, and based on the results of these experiments, analyzes the drift characteristics and patterns of the debris. Subsequently, employing a wealth of observational experimental data, three types of drift prediction models for the wreckage are established using the least squares method. These models include the AP98 model, the dynamics model, and an improved model. In conclusion, the effectiveness and accuracy of the three models is evaluated and analyzed using Monte Carlo techniques. The results indicate that the probability of positive crosswind leeway (CWL) is 47.4%, while the probability of negative crosswind leeway (CWL) is 52.6%. The jibing frequency is 7.7% per hour, and the maximum leeway divergence angle observed is 40.4 degrees. Among the three drift prediction models, the refined AP98 drift model demonstrates the highest forecasting precision. The findings of this study offer a more accurate drift prediction model for the search of an aircraft lost at sea. These results hold significant guiding importance for maritime search and rescue operations in the South China Sea.

Underpinning the ecological response of mixed chlorinated volatile organic compounds (CVOCs) associated with contaminated and bioremediated groundwaters: A potential nexus of microbial community structure and function for strategizing efficient bioremediation - Bashir Hussain; Jung-Sheng Chen; Shih-Wei Huang; I-Sen Tsai; Jagat Rathod; Bing-Mu Hsu (Environmental Pollution, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Exact artificial boundary condition and 1D time-domain method for seismic response analysis of layered saturated poroelastic half-space - Weihua Li; Sen Zheng; Shaoxiong Mu; Hang Mu; Yexin Wan (Soil Dynamics and Earthquake Engineering, 2023)

Performance and mechanisms for tetrabromobisphenol A efficient degradation in a novel homogeneous advanced treatment based on S2O42− activated by Fe3+ - Wei Song; Mu Li; Sen Xu; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Wenhui Qiu; Zhihong Wang; Qi Song; Kalpana Bhatt; Caixia Fu (Environmental Pollution, 2023)

Integrated toxicity assessment of DEHP and DBP toward aquatic ecosystem based on multiple trophic model assays - Lilai Yuan; Jia Liu; Ying Huang; Gongming Shen; Sen Pang; Chengju Wang; Yingren Li; Xiyan Mu (Environmental Science and Pollution Research, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Overexpression of LncRNA PSMG3-AS1 Distinguishes Glioblastomas from Sarcoidosis - Liusheng Chen; Guanliang Wang; Zihui Xu; Kailong Lin; Sen Mu; Yicheng Pan; Mengya Shan (Journal of Molecular Neuroscience, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Aluminum ammonium sulfate dodecahydrate purified from traditional Chinese medicinal herb Korean monkshood root is a potent matrix metalloproteinase inhibitor - Yehua Shen; Sen Liu; Fenghai Jin; Tianyang Mu; Cong Li; Kun Jiang; Weihua Tian; Dahai Yu; Yingqi Zhang; Xuexun Fang (BioMetals, 2012)

Molecular cloning and characterisation of a non-TIR-NBS-LRR type disease resistance gene analogue from sugarcane - Q. You-Xiong; L. Jian-Wei; Z. Ji-Sen; R. Miao-Hong; X. Li-Ping; Z. Mu-Qing (Sugar Tech, 2008)